Determinants of Personal Taxpayer Compliance: Evidence from North Badung Tax Office - Ni Putu Yuria Mendra; Putu Wenny Saitri; I Gusti Putu Eka Rustiana Dewi; Ni Komang Janitri Pratiwi; Ni Made Swinta Setiani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Taxes are the largest contributor to state revenue in financing national development. Tax compliance is the act of the taxpayer in fulfilling their tax obligations following the provisions of the legislation and tax implementation regulations in force in a country. Efforts made by the government to improve taxpayer compliance are by reforming tax laws and the tax administration system. This study aims to determine the effect of tax knowledge, tax sanctions, the benefit of the taxpayer identification number, and modern tax administration systems on personal taxpayer reporting compliance at the tax office in North Badung. The population of this research is personal taxpayers at the North Badung Tax Office Services, which is based on the data of individual taxpayers, as many as 95,542 people. The sample in this study consisted of 76 individual taxpayers who reported compliance, selected using a non-probability sampling method with an accidental sampling technique. The data analysis technique used is multiple linear regression analysis. The results showed that the tax knowledge variable did not affect personal taxpayer compliance, while the tax sanctions variable, the benefit of the taxpayer identification number, taxpayer awareness, and the modern tax administration system had a positive effect on personal taxpayer reporting compliance. Further research can expand on this study by incorporating other variables that, in theory, influence taxpayer reporting compliance, such as tax services.